Radical plurality on universal grounds. Issue 2 (16th July 2021) - Bobrowicz, Ryszard; Gustafsson Lundberg, Johanna
Abstract: This paper focuses on recent debates between the proponents of individualism and communitarianism. As the authors argue, the dichotomous character of these debates is inherently problematic, as no one functions just as an individual or member. Starting from the discussion around the Netflix series "Unorthodox" in the Swedish context, the authors engage with Sharon Todd's radical conception of plurality, and K.E. Løgstrup's notions of interdependence and the resulting ethical demand to show how these debates could be reframed into the constructive tension between plurality and universality.